2022
DOI: 10.3389/fninf.2022.883333
|View full text |Cite
|
Sign up to set email alerts
|

Fast Simulation of a Multi-Area Spiking Network Model of Macaque Cortex on an MPI-GPU Cluster

Abstract: Spiking neural network models are increasingly establishing themselves as an effective tool for simulating the dynamics of neuronal populations and for understanding the relationship between these dynamics and brain function. Furthermore, the continuous development of parallel computing technologies and the growing availability of computational resources are leading to an era of large-scale simulations capable of describing regions of the brain of ever larger dimensions at increasing detail. Recently, the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Authors of [ 30 ] reproduced the activity of 32 mm of a macaque cortex on 32 Tesla V100 GPUs. The parallel implementation achieved a speed-up of about 3 compared to the NEST simulator baseline.…”
Section: Resultsmentioning
confidence: 99%
“…Authors of [ 30 ] reproduced the activity of 32 mm of a macaque cortex on 32 Tesla V100 GPUs. The parallel implementation achieved a speed-up of about 3 compared to the NEST simulator baseline.…”
Section: Resultsmentioning
confidence: 99%
“…found that NEST simulation on the JURECA system (Thörnig, 2021) at the Jülich Supercomputing Centre was ≈ 15 times faster than simulation with GeNN on a single GPU (NVIDIA TITAN RTX). The recent work by Tiddia et al (2022) found that NEST GPU (parallel simulation on 32 GPUs, NVIDIA V100 GPU with 16 GB HBM2e) outperformed NEST (simulated on JUSUF HPC cluster Von St. Vieth (2021) and JURECA) by at least a factor of two. Kurth et al (2022) reported the real-time factor for the multi-layered model of a single cortical column introduced by Potjans and Diesmann (2014) with about N = 80, 000 neurons and 0, 3 • 10 9 synapses for a simulation with GeNN as RT = 0.7 (NVIDIA Titan RTX) and with NEST as RT = 0, 56 (cluster with 2 dual-processor machines with 128 cores each).…”
Section: Discussionmentioning
confidence: 99%
“…Knight and Nowotny (2021) found that NEST simulation on the JURECA system (Thörnig, 2021) at the Jülich Supercomputing Centre was ≈ 15 times faster than simulation with GeNN on a single GPU (NVIDIA TITAN RTX). The recent work by Tiddia et al (2022) found that NEST GPU (parallel simulation on 32 GPUs, NVIDIA V100 GPU with 16 GB HBM2e) outperformed NEST (simulated on JUSUF HPC cluster Von St. Vieth (2021) and JURECA) by at least a factor of two.…”
Section: Discussionmentioning
confidence: 99%
“…found that NEST simulation on the JURECA system (Thörnig, 2021) at the Jülich Supercomputing Center was ≈ 15 times faster than simulation with GeNN on a single GPU (NVIDIA TITAN RTX). The recent work by Tiddia et al (2022) found that NEST GPU (parallel simulation on 32 GPUs, NVIDIA V100 GPU with 16 GB HBM2e) outperformed NEST (simulated on JUSUF HPC cluster, Von St. Vieth, 2021, and JURECA) by at least a factor of two. Kurth et al (2022) reported the real-time factor for the multilayered model of a single cortical column introduced by Potjans and Diesmann (2014) with about N = 80, 000 neurons and 0, 3 • 10 9 synapses for a simulation with GeNN as RT = 0.7 (NVIDIA Titan RTX) and with NEST as RT = 0, 56 (cluster with two dual-processor machines with 128 cores each).…”
Section: Limitations Of the Present Studymentioning
confidence: 99%